2010
DOI: 10.1016/j.jcrs.2009.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity and higher-order aberrations with wavefront-guided and wavefront-optimized laser in situ keratomileusis

Abstract: Wavefront-guided LASIK and wavefront-optimized LASIK produced equivalent visual outcomes and no differences in HOAs. Wavefront-guided treatment could not be performed in many eyes because of difficulties during wavefront measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 18 publications
5
36
0
1
Order By: Relevance
“…Similarly, in some retrospective studies comparing VISX CustomVue with WaveLight Allegretto platforms in laser in situ keratomileusis 17 and PRK, 16,18 there was no significant difference in visual outcomes or induced HOAs. Although we did not include HOA RMS analysis in this study, our results closely match with other published results obtained by comparing both lasers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, in some retrospective studies comparing VISX CustomVue with WaveLight Allegretto platforms in laser in situ keratomileusis 17 and PRK, 16,18 there was no significant difference in visual outcomes or induced HOAs. Although we did not include HOA RMS analysis in this study, our results closely match with other published results obtained by comparing both lasers.…”
Section: Discussionmentioning
confidence: 92%
“…[13][14][15] It has been suggested that both lasers have a similar effect on the final HOA. 11,16,17 However, on review of the literature, no studies examining the effect of lasers on the Q value for PRK were found.…”
mentioning
confidence: 99%
“…12 Modern microkeratomes and femtosecond laser create more uniform, planar flaps 13,14 and recent reports have found equivalent visual outcomes between surface ablation and LASIK 5 and between wavefront-optimized or wavefront-guided LASIK for most patients. 15 This suggests that these flaps have minimal optical impact and therefore may be more amenable to amputation when necessary. Results may vary more for older flaps or those created with older generation microkeratomes, and this should be taken into consideration when planning amputation.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite recent advances in refractive surgery procedures, a small percentage of patients still have problems with their vision. [4][5][6][7] A recent study about LASIK Quality of Life published on the US Food and Drug Administration website 8 has shown that up to 4% of subjects were dissatisfied with their vision 3 months after LASIK surgery. In addition, this also caused a lot of difficulty with or even an inability to do normal activities in up to 1.0% of subjects not wearing correction.…”
mentioning
confidence: 99%